2021
DOI: 10.3390/toxics9050092
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Microbicidal Activity of Commonly Used Organic Solvents: A Comparative Study and Application to a Standardized Extract from Vaccinium macrocarpon

Abstract: The cytotoxicity and microbicidal capacity of seven organic solvents commonly applied for studying plant extracts and bioactive compounds were systematically investigated based on international standards. Four cell lines of normal (CCL-1, HaCaT) or tumor (A-375, A-431) tissue origin, seven bacterial and one fungal strain were used. The impact of the least toxic solvents in the determination of in vitro cytotoxicity was evaluated using a standardized extract from Vaccinium macrocarpon containing 54.2% v/v proan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The skin cell lines were purchased from CLS Cell Lines Service (GmbH, Eppelheim, Germany), and HEP-G2 cells were obtained from DSMZ (Deutsche Sammlung von Mikroorganismen und Zellkulturen, German Collection of Microorganisms and Cell Cultures GmbH, Braunschweig, Germany). Maintenance of cells followed the protocols described previously in [97].…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin cell lines were purchased from CLS Cell Lines Service (GmbH, Eppelheim, Germany), and HEP-G2 cells were obtained from DSMZ (Deutsche Sammlung von Mikroorganismen und Zellkulturen, German Collection of Microorganisms and Cell Cultures GmbH, Braunschweig, Germany). Maintenance of cells followed the protocols described previously in [97].…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…MTT assay was executed according to Annex C, ISO 10993-5 (ISO 10993-5:2009) for the evaluation of cytotoxic activity, as previously described [97], but there was exposure after treatment for 24 and 48 h in addition to the incubation for 72 h.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…In this sense, the recommended vehicles for solubilization of curcumin by the manufacturer are ethanol and dimethyl sulfoxide (DMSO). Although in many papers the effects of the solvents on culture viability are not shown [37,49,70] (or are not discussed [47,71,72]), if they do not present cytotoxic effects, the reality is that both vehicles produce effects that vary widely depending on the cell type and duration of treatment [71,[73][74][75]. The pre-established idea of the absence of the effects of these vehicles is recurrent in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…We first examine the cytotoxic effect of P. pterocarpum leaf extracts against B16-F1 mouse melanocyte cells. According to ISO 10993-5, any substance is regarded to have cytotoxic potential if the cell viability percentage is reduced to less than 70% of the untreated control (Ilieva et al, 2021;Nogueira et al, 2021). In this study, we found that both P. pterocarpum extracts did not exhibit any cytotoxic effect against B16-F1 mouse melanocyte cells (Figure 1) up to 4000 ng/mL.…”
Section: Discussionmentioning
confidence: 99%